PALEO- AND NEOTETHYAN MARGINS OCEANIC LITHOSPHERE REMNANTS REVEALED IN THE HIGH-GRADE BASEMENT OF THE EASTERN RHODOPE MASSIF, BULGARIA: U-PB ZIRCON AGE CONSTRAINTS AND GEODYNAMIC IMPLICATIONS - Bonev, Nikolay; Filipov, Petyo; Dotseva, Zornitsa (Ofioliti, 2024)
The eastern Rhodope Massif of Bulgaria concentrates meta-ophiolites of poorly known igneous ages, which offers the opportunity to examine the Tethyan oceanic floor and Eurasian plate margin interactions. MORB-type meta-mafic gabbro-basalt cross-cutting dykes and concordant layers to three meta-ultramafic bodies are enclosed in schist envelope. U-Pb zircon geochronology revealed crystallization ages of the dykes at 248 Ma and 245 Ma in one of the bodies, at 298 Ma for a layer at the contact of the second body and another layer at 160 Ma for the third body. Different Early Permian and Early Triassic crystallization ages of the bodies and another spatially close Late Devonian body, all witness for mantle lithosphere components that fall in the temporal range of the Paleotethys oceanic floor development and pre-Jurassic closure by subduction. As the different in age meta-ultramafic bodies are hosted by schist, this occurrence calls for a mélange related to the subduction-accretion history. This mélange telescoped during the subduction of the Paleotethys oceanic lithosphere under the Eurasian plate margin, to which accreted as early as the Middle Triassic. The mélange might well represent an element of the Paleotethys suture. The Late Jurassic crystallization age of a meta-gabbro at the contact of the third meta-ultramafic body in turn calls for the presence of Neotethys Ocean mantle lithosphere remnant, and is used to test the hypothesis for hidden mantle section of the Jurassic Evros ophiolite of the eastern Rhodope Massif. The answer is positive, and supported by the crystallization ages of the Evros ophiolite, the age of detrital zircons in the related Jurassic sedimentary successions, together with the Late Jurassic tectonic emplacement and age of inherited Triassic-Jurassic zircons in the meta-gabbro. Thus, a Paleotethys and Neotethys oceanic floor mantle lithosphere interacted with the Eurasian plate margin and their remnants have been revealed in the eastern Rhodope Massif.